2020
DOI: 10.1016/j.jvsv.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Practical diagnosis and treatment of suspected venous thromboembolism during COVID-19 pandemic

Abstract: A markedly increased demand for vascular ultrasound laboratory and other imaging studies in COVID-19epositive patients has occurred, due to most of these patients having a markedly elevated D-dimer and a presumed prothrombotic state in many of the very ill patients. In the present report, we have summarized a broad institutional consensus focusing on evaluation and recommended empirical therapy for COVID-19epositive patients. We recommend following the algorithms with the idea that as more data becomes availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(121 citation statements)
references
References 14 publications
1
113
0
7
Order By: Relevance
“…27 Another study shows that thrombosis-and bleeding-predicting tools are useful in the management of patients. 28 The study assessed the potential usefulness of Padua prediction score-to predict thrombosis risk-and the improved bleed risk assessment model-to predict risk of bleeding-in COVID-19 patients under thromboprophylaxis with UFH and LMWH. According to the bleeding predicting tool, nine (6.5%) patients had a high risk of bleeding (improved score !…”
Section: Bleeding and Bleeding Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Another study shows that thrombosis-and bleeding-predicting tools are useful in the management of patients. 28 The study assessed the potential usefulness of Padua prediction score-to predict thrombosis risk-and the improved bleed risk assessment model-to predict risk of bleeding-in COVID-19 patients under thromboprophylaxis with UFH and LMWH. According to the bleeding predicting tool, nine (6.5%) patients had a high risk of bleeding (improved score !…”
Section: Bleeding and Bleeding Riskmentioning
confidence: 99%
“…7), six of whom ($67%) experienced hemorrhagic events during the course of thromboprophylaxis, including mild or microscopic hematuria (n: 3), GI bleeding (n: 1), epistaxis (n: 1), and severe hemothorax (n: 1). 28 More detailed thromboprophylaxis of patients with COVID-19 and venous thromboembolism is outside the scope of this work and is presented elsewhere. 28 Anticoagulant therapy is contraindicated for patients with active bleeding and for those with a low platelet count (according to ISTH guidance < 25 Â 10 9 /L).…”
Section: Bleeding and Bleeding Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) causes coronavirus disease 2019 (COVID‐19) that manifests with variable severity 1 . A subset of symptomatic individuals develop proinflammatory or prothrombotic profiles requiring additional testing and interventions 2‐5 . It is unclear which COVID‐19 patients will ultimately develop severe disease that would have benefitted from early and aggressive interventions.…”
Section: Figurementioning
confidence: 99%
“…2 Since there is no consensus-approved treatment in this situation and considering the possibility of thrombosis associated with infection by coronavirus in certain cases, recently-acquired experience and findings of still-embryonic scientific studies has shown that effective anticoagulation can prevent or reverse the prothrombotic state in some patients. 2,3…”
Section: Introductionmentioning
confidence: 99%